Understanding a credit supply constraints among small scale enterprises in Kano State, Nigeria: A phenomenological approach - Balarabe, Ibrahim Inuwa; Samsudin, Shamzaeffa; Abdullah, Norehan (2018)
This paper examines factors that constrain small scale enterprises to access credit from microfinance banks (MFBs) and possible measures to tackle these constraints. It purposively sampled experts in the field of microfinance lending to respond on this issue through an interview from eight MFBs operating within the three political zones of Kano state; Kano central, Kano north and Kano south. As a result, four major constraints were identified which include – transaction cost constraint, internal constraint, socio-cultural constraint and environmental policy constraint – as being the key factors constraining small scale enterprises' ability to access credit. Though findings show different factors that constrain credit supply, but socioeconomic factor is prevalent according to participants’ response. The paper recommends strategies to address this issue to increase small scale business’s credit market participation.